Prevalence of irreversible pulpitis among male and female children - a retrospective study - SOH, NURUL HUSNIYAH BINTI CHE; JEEVANANDAN, GANESH; BALASUBRAMANIAM, ARTHI (The journal of contemporary issues in business and government, 2021)
Dental caries is one of the most common chronic diseases of adults and children in both developed and developing nations. The incidence of caries can cause irritation to the pulp and periradicular tissues which may result in inflammation. Inflammation over an extended period of time on the other hand can cause irreversible damage to the pulp. This study focuses on the prevalence of irreversible pulpitis among different genders of children. A retrospective cross- sectional study was conducted using the patient case records of a University hospital from June 2019 until March 2020, and children who were diagnosed with irreversible pulpitis were selected. Data was collected and then subjected to statistical analysis. Microsoft Excel 2016 data spreadsheet was used to collect data and later exported to the SPSS software. Among 244 children, males recorded slightly higher frequency with irreversible pulpitis, about 54% while females recorded approximately 46%. Based on age, 4-6 years children were more prevalent to irreversible pulpitis, surpassed 50% overall. The prevalence of irreversible pulpitis among children in this study seems to be slightly higher in males than female children.